Обгрунтування оптимальних режимів роботи удосконаленого зразка роторно-кавітаційного диспергатора при подрібненні рослинних кормів - Павліченко, В. М.; Лиходід, В. В.; Луц, П. М.; Січкарь, А. В.; Доруда, С. О.; Pavlichenko, V.; Lykhodid, V.; Lutz, Р.; Sichkar, А.; Doruda, S. (КНТУ, 2014)
Представлено результати експериментальних досліджень процесу диспергації компонентів кормових сумішей та відображено оптимальне поєднання факторів, які суттєво впливають на критерії оптимізації. Отримано математичні моделі другого порядку, які адекватно описують процес диспергації компонентів кормової суміші. Обґрунтовано оптимальні режими роботи удосконаленого зразка роторно-кавітаційного диспергатора та встановлено їх вплив на якісні та енергетичні показники робочого процесу подрібнення рослинних кормів при різноманітній їх композиції. Justification of optimal operating modes of created improved sample of rotary cavitation dispersant during the grinding plant feed. Presented the results of experimental studies of the process of grinding (dispersion) component of feed mixtures and displays the optimum combination of factors that significantly affect the optimization criteria. Obtained mathematical models of the second order, which adequately describe the process of dispersion component of feed mixture. Proved optimal modes of advanced sample of rotary cavitation dispersant and established their influence on the quality and energy performance of working crushing process plant feed at a variety of their composition. The results of experimental research is the foundation for further improvement work of the existing structures of dispersants of similar purpose.
Justification of optimal operating modes of advanced design rotary cavitation dispersant during the grinding plant feed
Keywords: рослинні корми; роторно-кавітаційний диспергатор; удосконалений зразок; подрібнення; оптимальні режими; обґрунтування; plant foods; rotary-cavitation dispersant; an improved sample; grinding; optimal modes; justification